Constraints on non-Standard Model Higgs boson interactions in an effective Lagrangian using differential cross sections measured in the H→γγ decay channel at s√=8 TeV with the ATLAS detector - Aad, G. (2016)
The strength and tensor structure of the Higgs boson´s interactions are investigated within an effective field theory framework, which allows new CP-even and CP-odd interactions that can lead to changes in the kinematic properties of the Higgs boson and associated jet spectra. The parameters of the effective field theory are probed using a fit to five differential cross sections previously measured by the ATLAS experiment in the H→γγ decay channel with an integrated luminosity of 20.3 fb−1 at s√=8 TeV. In order to perform a simultaneous fit to the five distributions, the statistical correlations between them are determined by re-analysing the H→γγ candidate events in the proton-proton collision data. No significant deviations from the Standard Model are observed and limits on the effective field theory parameters are derived. The statistical correlations are made publicly available to allow for future analysis of theories with non-Standard Model interactions.